ChemInform Abstract: Recent Approaches for Bridging the Pressure Gap in Photoelectron Microspectroscopy. Issue 16 (March 2016) - Kolmakov, Andrei; Gregoratti, Luca; Kiskinova, Maya; Gunther, Sebastian
Abstract: Review: 103 refs.